Surface ultrastructure of Blastocystis sp. isolated from cattle - NI KOMANG APRILINA WIDISUPUTRI; NUNUK DYAH RETNO LASTUTI; ENDANG SUPRIHATI; POEDJI HASTUTIEK; HANI PLUMERIASTUTI; MUFASIRIN MUFASIRIN; HENI PUSPITASARI; Lucia Tri Suwanti (Society for Indonesian Biodiversity, 2021)
Abstract. Widisuputri NKA, Lastuti NDR, Suprihati E, Hastutiek P, Plumeriastuti H, Mufasirin, Puspitasari H, Suwanti LT. 2021. Surface ultrastructure of Blastocystis sp. isolated from cattle. Biodiversitas 22: 1514-1518. Blastocystis sp is a protozoan parasite commonly detected in the intestinal tract of humans and various animals that causes zoonotic blastocystosis. The pathogenic potential of Blastocystis is still being evaluated, some Blastocystis sp are completely pathogenic, while others can be considered commensal and hypothetical, related to the role of the surface coat of Blastocystis sp. This study aimed to compare the surface ultrastructure of Blastocystis sp. in cattle with diarrhea and non diarrhea by Scanning Electron Microscope (SEM). Four Blastocystis sp. isolates were selected from the faeces of four positives cattle which consisted of two diarrhea and two non-diarrhea cattle. The result showed that Blastocystis sp. in cattle appeared in round shape and reproduced by binary fission.  The surface cell of Blastocystis sp. isolates from diarrhea cattle had a rough surface while organism of non diarrhea cattle isolates was very smooth. Bacteria were seen attached to the surface of Blastocystis sp. from diarrhea cattle faeces. In conclusion, the features of the surface structure of Blastocystis sp. correlated with symptomatic appearance. The surface structure of Blastocystis sp. isolates from cattle with diarrhea was rougher than non diarrhea.